Regular Econometric Model of Taylor for Albania - Misha, Ergys (European Journal of Economics and Business Studies, 2016)
The Taylor’s Rule Central Banks is applying widely today from Central Banks for design the monetary policy and for determination of interest rates. The purpose of this paper is to assess monetary policy rule in Albania, in view of an inflation targeting regime. In the first version of the Model, the Taylor’s Rule assumes that base interest rate of the monetary policy varies depending on the change of (1) the inflation rate and (2) economic growth (Output Gap).Through this paper it is proposed changing the objective of the Bank of Albania by adding a new objective, that of "financial stability", along with the “price stability”. This means that it is necessary to reassess the Taylor’s Rule by modifying it with incorporation of indicators of financial stability. In the case of Albania, we consider that there is no regular market of financial assets in the absence of the Stock Exchange. For this reason, we will rely on the credit developmet - as a way to measure the financial cycle in the economy. In this case, the base rate of monetary policy will be changed throught: (1) Targeting Inflation Rate, (2) Nominal Targeting of Economic Growth, and (3) Targeting the Gap of the Ratio Credit/GDP (mitigating the boom cycle, if the gap is positive, and the contractiocycle if the gap is negative).The research data show that, it is necessary that the Bank of Albania should also include in its objective maintaining the financial stability. In this way, the contribution expected from the inclusion of credit gap indicators in Taylor’s Rule, will be higher and sustainable in time.